High-Power Rapid Laser-Induced Synthesis of Multi-functional Cobalt Metal-Organic Framework With an Unprecedented Synthesis Efficiency - Mutlu, Saliha; Ortac, Bulend; Karatutlu, Ali; Gorkan, Taylan; Durgun, Engin; Soyler, Dilek; Soylemez, Saniye; Lillepag, Jelena; Filiz, Volkan; Arsu, Nergis; Yilmaz, Sevil Savaskan (WILEY-V C H VERLAG GMBH, 2026)
A rapid, high-yield laser-assisted synthesis route with an exceptional production efficiency (>= 90%) is introduced for cobalt-based metal-organic frameworks (Co-MOFs), producing ordered hybrid structures within an hour that integrate optical, magnetic, and adsorption functionalities. The Co-MOFs exhibit tunable properties, including a low-temperature paramagnetic transition confirmed by magnetic measurements and first-principles calculations. Gas adsorption studies reveal promising performance for N2, CH4, and CO2, combining low energy consumption with cost-effective gas separation. Structural analysis indicates mesoporosity with high accessibility, supporting selective uptake under practical conditions. Importantly, Co-MOF-modified graphite electrodes demonstrate outstanding electrochemical sensing performance for dopamine, achieving a low detection limit (5.5 & micro;M), high sensitivity (121 & micro;A mM- 1 cm- 2), and excellent reproducibility in human serum. These results underline the multifunctional potential of laser-synthesized Co-MOFs as scalable platforms that couple sustainable gas separation with biomedical diagnostics, advancing the development of framework materials for real-world applications.
Keywords: density functional theory (DFT); electrochemical sensing; laser technique; metal-organic framework; Rietveld analysis; ELECTROCHEMICAL SENSOR; ADSORPTION PROPERTIES; PRESSURE ADSORPTION; FILMS; OXIDE; CO2; NITROGEN; METHANE; MOFS; Materials Science